Effects of composition and particle size of crystallization on physical properties of Java's marble composite / Irzaman, S. Nurhasanah and Z. Jamal - ., Irzaman; S., Nurhasanah; Jamal, Z. (2006)
Composite tile was made using Java’s marble particles (CaCO3), phenol resin and as a catalyst was used hexamethylenetetramine (HEXA), then using simple mixing method based on volume variation from 62.50 ml to 125.00 ml between matrix and hardener, based on mesh variation consisted of 25 mesh, 40 mesh and 60 mesh. Samples were dried in a room temperature for 3 hours. The compressive strength and crystal structure were analysed. The results showed that compressive strength values were in range 6.15 x 107 N/m2 - 9.61 x 107 N/m2 , and there were two crystal structures consisted of marble crystal and phenol crystal. Crystal structure analysis of CaCO3 was carried out by using the Rietveld semiquantitative analysis. The final crystal structure was rhombohedral and lattice constant were a = b = 4.989 A, c = 17.042 A; (figures of merit were: Rp = 10.43 %; Rwp = 15.35 %, GOF = 3.49; RB = 3.94 % (marble): RB = 4.09 % (50 % of marble particle); RB = 4.12 % (60 % of marble particle); RB = 4.14 % (67 % of marble particle). The results of characterising indicated the composites and marble were able to use for making tile because they were lighter, stronger and the amount of crystals increased if compared with pure marble only.